2012
DOI: 10.2174/187152312803476282
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Properties of Drugs from saffron crocus

Abstract: The medicinal uses of saffron (Crocus sativus Linnaeus) have a long history beginning in Asian countries since the Late Bronze Age. Recent studies have validated its potential to lower the risk of several diseases. Some metabolites derived from saffron stigmas exert numerous therapeutic effects due to hypolipidemic, antitussive, antioxidant, antidiabetic activities and many others. Water and ethanol extracts of Crocus sativus L. are cardioprotective and counteract neurodegenerative disorders. Many of these med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 74 publications
1
64
0
1
Order By: Relevance
“…Stigmas were harvested from mature flowers (C. sativus L; Iridaceae) [119]. Pharmacological studies on saffron demonstrated numerous health properties such as anticancer and antitoxic [120], antioxidant [121], antinociceptive and anti-inflammatory [122], antiatherosclerosis [123], antidiabetic and insulin resistance [124], hypotensive [125], hypolipidemic [126], hypoglycemic [127], and antidepressant and mood improving [128]. It is a source of plant polyphenols and carotenoids.…”
Section: Saffronmentioning
confidence: 99%
“…Stigmas were harvested from mature flowers (C. sativus L; Iridaceae) [119]. Pharmacological studies on saffron demonstrated numerous health properties such as anticancer and antitoxic [120], antioxidant [121], antinociceptive and anti-inflammatory [122], antiatherosclerosis [123], antidiabetic and insulin resistance [124], hypotensive [125], hypolipidemic [126], hypoglycemic [127], and antidepressant and mood improving [128]. It is a source of plant polyphenols and carotenoids.…”
Section: Saffronmentioning
confidence: 99%
“…Bitter substances derived from safranal and crocin carotenoid pigment (an important component of saffron stigma) are said to have pharmacological effects (7,8). Some studies investigated the many medicinal applications of saffron including induction of abortion (9), increasing uterine contractions (10,11), analgesic and antiinflammatory properties (12)(13)(14), anti-anxiety (15)(16)(17), sedation (18), and labor pain (19). Authors' recent trial also showed that oral capsules of saffron increased the Bishop score in term pregnant females with no labor pain (20).…”
Section: Introductionmentioning
confidence: 99%
“…A natural carotenoid of saffron, crocin, is responsible for its beneficial effects including anti-oxidant (Tseng et al 1995), anti-inflammatory (Poma et al 2012), and anti-tumoral properties, demonstrated in some cancer cell lines and animal models (Abdullaev 1994;Dhar et al 2009;Magesh et al 2006). Bathaie and colleagues (Bathaie et al 2013) demonstrated that this ancient herbal medicine can be used against gastric adenocarcinoma in both human and the rat model (Bathaie et al 2013).…”
Section: Saffronmentioning
confidence: 99%